Universals, Absolutes and Inalienables: the Indestructible Rights - Álvarez Gálvez, Íñigo (Revista de Humanidades de Valparaíso, 2014)
There is a particular moral theory in which human rights are conceived as indestructible rights (as inalienable, universal and absolute rights). Using Dworkin’s words we could say this is a good way of taking rights seriously. However, we may also ask whether there is another way of taking rights as seriously as Dworkin says without being a supporter of that theory. From this point of view, perhaps human rights cannot be considered neither as absolute (in the sense that they cannot be defeated in any circumstances); nor universally valid (unless we first sort out the problem about the validity of the moral and the legal systems); and not even inalienable. Can this proposal be seen as another way of taking rights seriously?